THE DESCRIPTIVE ANALYSIS OF YOUTUBE LEARNING VIDEO ON STUDENTS' COMPETENCE IN UNDERSTANDING READING NARRATIVE TEXT AT THE NINTH GRADE OF UPTD SMP NEGERI 2 GUNUNGSITOLI UTARA - Harefa, Stevani Aurelya; Waruwu, Yaredi; Harefa, Trisman; Harefa, Afore Tahir (FKIP Unismuh Makassar, 2024)
This research aims to analyze students' competence in understanding narrative texts through YouTube learning videos and to compare students' reading abilities before and after using these learning videos. This research was conducted on class IX-A students at UPTD SMP Negeri 2 Gunungsitoli Utara. There were 23 students, consisting of 13 men and 10 women. This research uses a qualitative descriptive method. Data was obtained through questionnaires and documentation. Questionnaires were given to identify students' perceptions regarding the effectiveness of YouTube videos as a learning medium, while documentation was used to see differences in students' reading scores before and after using videos. The results showed that the use of YouTube videos significantly improved students' understanding of narrative texts, with an increase in reading scores after using the videos. The use of videos also provides a more enjoyable learning atmosphere, increases motivation, and makes it easier for students to master narrative text material.